2019
DOI: 10.1371/journal.pone.0222982
|View full text |Cite
|
Sign up to set email alerts
|

“I put it in my head that the supplement would help me”: Open-placebo improves exercise performance in female cyclists

Abstract: This study investigated the effect of open-placebo on cycling time-trial (TT) performance. Twenty-eight trained female cyclists completed a 1-km cycling TT following a control session or an open-placebo intervention. The intervention consisted of an individual presentation, provided by a medic, in which the concept of open-placebo was explained to the participant, before she ingested two red and white capsules containing flour; 15 min later, they performed the TT. In the control session, the participant sat qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Using the identical questionnaire to identify participants with a high belief in placebos, Leibowitz et al [44] demonstrated that OLPs reduced physiological effects for participants who strongly believe in placebos. High interindividual variations when examining effects of OLPs have also been reported in other studies (e.g., [34]).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Using the identical questionnaire to identify participants with a high belief in placebos, Leibowitz et al [44] demonstrated that OLPs reduced physiological effects for participants who strongly believe in placebos. High interindividual variations when examining effects of OLPs have also been reported in other studies (e.g., [34]).…”
Section: Discussionsupporting
confidence: 71%
“…Recent studies have shown that OLPs may also help people with non-clinical problems. For example, it has been demonstrated that OLPs improve exercise performance in cyclists [34]. Furthermore, we recently reported reduced test anxiety and improved self-management abilities in students when receiving OLPs [35].…”
Section: Introductionmentioning
confidence: 75%
“…Out of twenty-six published non-deceptive placebo studies to date, eight included objective behavioral or biological measures. Only one of these eight studies showed an effect on behavioral outcomes, and no direct effects on biological outcomes have been documented 10 , 17 21 (see Supplementary Table 1 for a current list of non-deceptive placebo studies). Therefore, it remains unclear whether the beneficial effects associated with non-deceptive placebos represent genuine psychobiological effects 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Double-blind studies have shown that participants receiving a placebo treatment perceived to be caffeine improved exercise performance to a similar extent when compared with caffeine ingestion [13,14]. Positive expectation associated with caffeine ingestion appeared to drive this effect since individuals correctly believing that they had ingested caffeine improved to a greater extent than the average effect of caffeine [13,15]. However, these results were not observed in physiological variables, such as heart rate and blood pressure [16], further reinforcing the notion that the expected effect of caffeine plays a subjective role in the belief around its consumption [16,17].…”
Section: Introductionmentioning
confidence: 99%